Relationship of Water Media Characteristics (pH, Temperature, TDS) to Density of Aedes sp Mosquito Flars in Karanggeneng Village, Lamongan District - Dwi Maghfiroh, Andini; Syakbanah, Nur Lathifah; Eko, Sulistiono; Hanif, Muhammad (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
DHF (Dengue hemorrhagic fever) is a tropical endemic disease in Indonesia with a fluctuating trend in Lamongan. The main factor under control is the larval breeding habitat. This study aimed to determine the relationship between the characteristics of the water medium and the density of Aedes sp. mosquito larvae in Karanggeneng Village, Lamongan Regency. We conducted this quantitative study using a cross-sectional observational method on a sample of 80 houses in Karanggeneng Village, employing a straightforward random sampling technique. We recorded the data collection in the observation sheet and analyzed it with a chi-square test. The results showed that 37 houses were positive for Aedes sp. larvae based on HI (DF = 6), CI (DF = 6), and BI (DF = 7), so Karanggeneng Village has a high mosquito larval density. There is a significant relationship between water media and the presence of Aedes sp. mosquito larvae. The relationship between pH (p-value = 0.000), temperature (p-value = 0.000), and TDS (p-value = 0.000) is significant. We recommend regularly draining the water container weekly to prevent mosquito larvae from using it as a habitat.